Multifunctional Copper-Containing Mesoporous Glass Nanoparticles as Antibacterial and Proangiogenic Agents for Chronic Wounds - Paterson, Thomas E.; Bari, Alessandra; Bullock, Anthony J.; Turner, Robert; Montalbano, Giorgia; Fiorilli, Sonia; Vitale-Brovarone, Chiara; MacNeil, Sheila; Shepherd, Joanna (Frontiers in Bioengineering and Biotechnology, 2020)
The physiological wound healing process involves a cascade of events which could be affected by several factors resulting in chronic, non-healing wounds. The latter represent a great burden especially when bacterial biofilms are formed. The rise in antibiotic resistance amongst infectious microorganisms leads to the need of novel approaches to treat this clinical issue. In this context, the use of advanced biomaterials, which can enhance the physiological expression and secretion of the growth factors involved in the wound healing process, is gaining increasing attention as a robust and appealing alternative approach. Among them, mesoporous glasses are of particular interest due to their excellent textural properties and to the possibility of incorporating and releasing specific therapeutic species, such as metallic ions. One of the most attractive therapeutic ions is copper thanks to its proangiogenic and antibacterial effects. In this contribution, copper containing mesoporous glass nanoparticles were proposed as a multifunctional device to treat chronic wounds. The developed nanoparticles evidenced a very high specific surface area (740 m2/g), uniform pores of 4 nm and an almost total release of the therapeutic ion within 72 h of soaking. The produced nanoparticles were biocompatible and, when tested against Gram positive and Gram negative bacterial species, demonstrated antibacterial activity against both planktonic and biofilm bacteria in 2D cell monolayers, and in a 3D human model of infected skin. Their proangiogenic effect was tested with both the aortic ring and the chick chorioallantoic membrane assays and an increase in endothelial cell outgrowth at a concentration range between 30 and 300 ng/mL was shown. Overall, in this study biocompatible, multifunctional Cu-containing mesoporous glass nanoparticles were successfully produced and demonstrated to exert both antibacterial and proangiogenic effects.